Analysis of contact forces between the pantograph and the overhead conductor rail using a validated finite element model. (15th December 2020) - Simarro, Montserrat; Postigo, S.; Prado-Novoa, Maria; Pérez-Blanca, A.; Castillo, Juan J.
Highlights: Contact forces of 2 OCR sections and 11 pantographs at 70, 100 & 130 Km/h. Span length and pantograph have little influence on contact forces at low speed. Irregular OCR spans increase contact forces at medium and moderately high speed. Contact forces amplification occurs at 70 Km/h due to pantograph resonances. The speed increase yields higher contact forces in section transitions. Abstract: This work presents the study of the interaction between 11 models of pantographs and 2 models of overhead conductor rails (OCR). All the models have been analysed at speeds of 70, 100 and 130 km/h. Furthermore, one of the OCR models used to carry out this study has been previously validated with experimental modal tests. The contact forces between each pantograph and catenary model is obtained in all cases. The analysis of the results reveals the contact forces are influenced by the dispersion in the length of the spans of the OCR sections and the pantograph model for speeds above 100 km/h. Thus, if pantograph resonance is not present, the lower the dispersion, the more constant the forces are. On the contrary, span length variations and the pantograph model have little influence on contact forces at low speeds. In addition, contact forces increase in the transitions between two sections of the overhead conductor rail. This phenomenom becomes more noticeable as the speed of pantograph operation increases.